New Approaches to Spanish Dialectal Grammar: Guest Editor’s Introduction - Enrique Pato (Languages, 2024)
If we understand Language as everything that is selected, numbered, merged and sent, and Grammar (both of the language and of the individual) as the union of Lexicon and Syntax, we share the same theoretical vision [...]